MODERATING ROLE OF MANAGERIAL EFFICIENCY IN THE RELATIONSHIP BETWEEN CORPORATE SOCIAL RESPONSIBILITY AND MARKET VALUE OF BANKS IN NIGERIA - Johnson, Emily; Lee , Richard; Zhang , Sophie (Ayden International Journal of Banking, Finance and Technology, 2024)
This research paper investigates the moderating effect of managerial efficiency (ME) on the association between corporate social responsibility (CSR) and market value of Nigerian banks, incorporating four control variables. The paper utilized a panel data of eight Nigerian listed banks over the study period 2010- 2021. Static panel techniques such as Pooled Ordinary Least Squares (POLS) and the Fixed Effects Model (FEM) in conjunction with the Weighted Least Squares (WLS) were considered in the model estimation However, the Restricted F-test rated the POLS over the FEM, which was later dropped for WLS due to heteroskedasticity problem. The main findings reveal that CSR has a significant positive effect on the market value; ME has a positive and significant effect on the market value and ME significantly and negatively moderates the link that binds CSR and the market value. The research concludes that the role of ME matters when it comes to understanding the CSR and the market value nexus. Expenditure on CSR activities should be multiplied by banks, as doing so will create good image, loyalty and reputations for the banks, and consequently improve their market value.